Serial extraction in the context of interceptive orthodontics (Research, Society and Development, 2023)
The purpose of this work is to present the protocol of serial extractions through a literature review, as well as its diagnosis, indications, contraindications, and execution techniques in clinical practice. This study was consolidated through a literature review encompassing national and international scientific studies made available through two database platforms: PubMed and Google Scholar, using the descriptors: “serial extractions”; “orthodontics”; “interceptive” and selecting articles in the following languages: English, Portuguese and Spanish, from the year 2012, including classic articles from previous years. As main results, it was observed that the most traditional extraction technique consists of a reversible phase, where the deciduous anterior teeth are removed to allow the spontaneous alignment of the permanent incisors, and an irreversible phase, which may or may not be performed, where extraction of a permanent tooth to dissolve crowding in the posterior segment of the arch. The main indication is for patients with Class I malocclusions with negative discrepancy, and it is contraindicated for Class II and III malocclusions. This technique has the advantage of reducing the period of mechanical treatment and retention in the corrective phase. Disadvantages include lingualization of lower incisors, increased overbite with consequent deepening of the curve of Spee. Thus, it can be concluded that the serial extraction protocol is an ally in the clinical routine to intercept the development of dental crowding, but it needs to be well diagnosed, have a correct indication and managed according to a predetermined sequence.